2008
DOI: 10.1021/ac7025892
|View full text |Cite
|
Sign up to set email alerts
|

Effective Path Length in Attenuated Total Reflection Spectroscopy

Abstract: Attenuated total reflection (ATR) spectroscopy is now the most popular sampling technique for the measurement of infrared spectra of condensed phase samples. Most practitioners of ATR spectroscopy use the equation for depth of penetration, d(p), to estimate the path length of the evanescent wave through the sample. However, the effective path length, d(e), of the evanescent wave in an ATR measurement, i.e., the equivalent path length in a transmission measurement that would lead to an absorption band of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 7 publications
2
77
0
Order By: Relevance
“…Both the real part and the imaginary part of the refractive index change as a function of λ in proximity of the sample absorption peaks 24. This is particularly relevant for the strong absorption peaks characteristic of PMMA for which the influence of the extinction coefficient on d p cannot be neglected 24, 26. It should be noted that, contrary to the first PTIR reports,14 where light was transmitted through the sample and totally reflected at the sample‐air interface, the experimental conditions used here ( θ = 45°, n 1 = 2.438, n2 ( λ ) = 1.2 to 1.65, k 2 ( λ ) = 0 to 0.4)24 ensure that total internal reflection is achieved at all wavelengths (from 1800 cm −1 to 1200 cm −1 ) at the prism‐sample interface.…”
Section: Resultsmentioning
confidence: 99%
“…Both the real part and the imaginary part of the refractive index change as a function of λ in proximity of the sample absorption peaks 24. This is particularly relevant for the strong absorption peaks characteristic of PMMA for which the influence of the extinction coefficient on d p cannot be neglected 24, 26. It should be noted that, contrary to the first PTIR reports,14 where light was transmitted through the sample and totally reflected at the sample‐air interface, the experimental conditions used here ( θ = 45°, n 1 = 2.438, n2 ( λ ) = 1.2 to 1.65, k 2 ( λ ) = 0 to 0.4)24 ensure that total internal reflection is achieved at all wavelengths (from 1800 cm −1 to 1200 cm −1 ) at the prism‐sample interface.…”
Section: Resultsmentioning
confidence: 99%
“…) is nearly a linear function of the wavenumber. 69 Using this approximation and assuming molar absorption coefficients determined from solution are valid in the bulk, the PE-g and PE-v compositions were quantified using Equations 1-3:…”
Section: Samplementioning
confidence: 99%
“…Averett and Griffiths [27] showed that for a ZnSe IRE with q ¼ 45 and n 2 ¼ 1.5, the average value of d e,s and d e,p is approximately equal to 2d p . Thus, in this work the path length (b) was assumed to be equal to 2d p .…”
Section: Infrared Spectroscopy Analysismentioning
confidence: 99%